Association of Stress Level with Menstrual Disturbance Among Female Students in Medical Faculty Sriwijaya University - Fildzah Hashifah Taufiq; Herry Hasnawi; Rachmat Hidayat (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2019)
Association Of Stress Level With Menstrual Cycle Disturbance Among Female Students In Medical Faculty Of Sriwijaya University. Menstruation occurs regularly every month will form a menstrual cycle. Normal menstrual cycles in women range from 21-35 days. However, the menstrual cycle is not always normal, many women experience menstrual disturbance. Menstrual cycle disturbance are caused by several factors, which is stress. This study aims to analyze the association of stress level with menstrual cycle disturbance among female students in Medical Faculty of Sriwijaya University. This study is analytical cross-sectional study with primary data from menstrual cycle, stress ISMA, personality type DSM V questionnaires.. In this study, 503 samples are fulfilled inclusion criteria. Among 503 subjects, 59 (11.7%) female students experienced polymenorrhea, 391 (77.7%) female students had normal menstrual cycles, 53 (10.6%) female students experienced olygomenorrhea. Chi Square test showed that there was an association between stress level and menstrual cycle disturbance. There is a significant association between between stress level and menstrual cycle disturbance among female students in Medical Faculty of Sriwijaya University. Keywords: Stress level, Menstrual cycle disturbance.